Chapter 1 Teaching in the Shadow - Hollins, Etta R. (Taylor & Francis, 2019)
For preservice candidates and novice teachers facing the challenges of feeling underprepared to teach in urban schools, this book offers a framework for conceptualizing, planning, and engaging in powerful teaching. Veteran teacher educator Etta Ruth Hollins builds on previous work to focus on transformative practices that emphasize the purpose and process of teaching. These practices are designed to improve academic performance, transform the social context in low-performing urban schools, and improve the quality of life in the local community. The learning experiences provided in this book guide readers through a sequence of experiences for learning about the local community that include an examination of history and demographics, community resources, local city and federal governance structures, and collaborating with other professionals. Focus Questions and a dedicated Application to Practice section in each chapter further guide learning and help make real-world connections. Designed to enable readers to bridge the gaps between theory and practice and the actual needs of urban students and their communities, this groundbreaking text helps prepare preservice candidates to make a successful transition and aids novice teachers in developing teaching practices that support academic excellence. Table of Contents